PENGGUNAAN LIST OF VALUES (LOV) UNTUK MEMAHAMI PERILAKU KONSUMEN - Hari, Abdul Hadi (Kiat Bisnis, 2015)
The role of personal values for marketing is very important because personal values directly affect consumer interest and behavior. Attaching personal values of a product can make the products have some positive effects incorporated in value. List Of Values (LOV) becomes optimal segmentation instrument because it can help to understand the basic nature of the consumers. LOV consists of nine values are: Sense of belonging, Warm relationship with other, Excitement. Fun and enjoyment in live. Self-fulfillment, Sense of accomplishment. Being well respected. Security. and Self-respect.Keywords: values, personal, LOV, consumer